Challenges of Penta Helix Collaboration in Kandua Raya Waterfall Tourism Development, Kedang Ipil - Niken Nurmiyati; Arnold Arswenda Kusuma; Carolina Irene Andalia; Muhammad Reza Fahlevi Ramadana (Universitas Muhammadiyah Sorong, 2026)
This study aims to analyze the Penta Helix collaboration in the development of Kandua Raya Waterfall tourism in Kedang Ipil Village, Kutai Kartanegara Regency. Kandua Raya Waterfall has significant potential as a nature and culture-based ecotourism destination due to its natural beauty, biodiversity, and the identity of the indigenous community. However, its development still faces various challenges, including limited infrastructure, low investment, weak stakeholder coordination, and threats of land conversion caused by the expansion of oil palm plantations and mining activities. This study employed a qualitative approach using in-depth interviews, field observations, and documentation studies as data collection techniques. The data were analyzed thematically to identify the roles, contributions, and obstacles faced by each actor within the Penta Helix framework, consisting of government, academia, the private sector, communities, and the media. The findings reveal that the government, communities, academia, and media have actively contributed to tourism development, while the private sector remains suboptimal and tends to prioritize extractive industries. Therefore, strengthening multi-stakeholder collaboration, enhancing community capacity, and implementing environmental protection policies are essential to achieve sustainable tourism development.